CORRELATION BETWEEN THE LENGTH OF THE DENTAL ROWS AND THE TOPOGRAPHOANATOMIC INDICATORS OF THE ARTICULAR DISK (MENISCUS) IN THE PATIENTS WITH DYSFUNCTIONAL CONDITIONS ACCORDING TO MRI DATA - Y.S. Lunkova; O.B. Tumakova; V.M. Novikov (Український стоматологічний альманах, 2018)
Objective is to investigate the interconnections of the mesiodistal dimensions of occlusal surfaces of teeth and structural elements of the temporomandibular joint with its internal disorders.